2010
DOI: 10.1259/bjr/29140440
|View full text |Cite
|
Sign up to set email alerts
|

The value of multidetector-row CT angiography for pre-operative planning of breast reconstruction with deep inferior epigastric arterial perforator flaps

Abstract: The deep inferior epigastric artery perforator (DIEP) flap has recently become the first option for breast reconstruction. However, the anatomy of the deep inferior epigastric artery varies greatly from one individual to another and even from one hemiabdomen to the other. An optimal pre-operative evaluation method that adequately maps the underlying vasculature has been lacking. The advent of multidetector-row CT (MDCT) angiography has proven highly accurate at detailing the vasculature, but no reports have do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 11 publications
0
32
0
1
Order By: Relevance
“…After screening the full text of 20 articles, eight were selected for critical appraisal (Fig. ) . No additional relevant studies were found by screening related articles and citations.…”
Section: Resultsmentioning
confidence: 99%
“…After screening the full text of 20 articles, eight were selected for critical appraisal (Fig. ) . No additional relevant studies were found by screening related articles and citations.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also reported that they did not make any intraoperative changes to the preoperative planning of these 22 patients. 11 Furthermore, Piorkowski et al evaluated SIEA adequacy of 113 patients based on pCTA and compared the results to operative dissection and determined that 50% of patients who were found to have at least one adequate SIEA on pCTA had a single breast reconstructed with an SIEA flap. 12 The differences in accuracy of pCTA between studies available in the literature can be attributed to variations in patient population, surgeons' preference, and interpretation of operative or CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][17][18][19][20]26,38 The DIEP flap is associated with a steep learning curve, 39 a relatively tedious flap dissection, and a higher rate of flap complications than TRAM flap harvest. Presurgical imaging may, therefore, allow flap complications to be reduced while maintaining the benefit of reduced donor site morbidity.…”
Section: Discussionmentioning
confidence: 99%